Solubility Kinetics Study of Organic and Inorganic Mercury Species in Reservoir Fluids and Their Behaviour in Aqueous Environments - Kho, Fenny Anggreni (Curtin University, 2018)
Mercury is present as trace contaminants in various gas reservoirs. Dynamic solubility of HgCl2 and Ph2Hg mercury have been investigated in this work. Parameters involving absorption characteristics and reaction kinetics were evaluated in solutions of varying NaCl and MEG. Findings have been utilised to address emission pathways and behaviour of mercury species within reservoir fluids and waste streams. This knowledge will aid in development of effective mercury management within the oil and gas industry.